1999
DOI: 10.1161/01.cir.99.16.2073
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Myocardial Perfusion Imaging and Cardiac Troponin I in Patients Admitted to the Emergency Department With Chest Pain

Abstract: Early perfusion imaging and serial cTnI have comparable sensitivities for identifying myocardial infarction. Perfusion imaging identified more patients who underwent revascularization or who had significant coronary disease, but it had lower specificity. The 2 tests can provide complementary information for identifying patients at risk for ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(55 citation statements)
references
References 33 publications
0
50
0
5
Order By: Relevance
“…Some studies even mention that optimal sensitivity of troponin is not reached before 18 hours of symptom onset [13][14][15][16][17][18] . In our study, we found that Troponin I measurements at admission had a sensitivity of 68.8% compared to a 86% sensitivity of scintigraphy during chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies even mention that optimal sensitivity of troponin is not reached before 18 hours of symptom onset [13][14][15][16][17][18] . In our study, we found that Troponin I measurements at admission had a sensitivity of 68.8% compared to a 86% sensitivity of scintigraphy during chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Acute coronary syndrome was confirmed if there was development of acute myocardial infarction or documentation of significant coronary artery disease that required urgent revascularization. 8,9 Myocardial contrast echocardiography: Intravenous MCE was performed with a Sonos 5500 instrument (Philips Medical Imaging, Andover, Massachusetts) with harmonic Figure 1. MCE using power harmonic Doppler imaging with a 2-trigger mode.…”
Section: Methodsmentioning
confidence: 99%
“…Despite its potential limitations, urgent revascularization has been used as an end point in previous studies of unstable angina. 8,9 We excluded patients who had previous myocardial infarction because perfusion imaging is unable to differentiate among acute ischemia, acute myocardial infarction, and previous myocardial infarction. 9,18 However, the distinction between previous infarction and acute ischemia can be clinically made in most patients.…”
Section: Mce Versus Electrocardiography Troponin and Echocardiographymentioning
confidence: 99%
“…Although multimarker strategies (7,8 ), myocardial perfusion imaging (9 ), and carefully developed clinical pathways that integrate all of the above elements (10 ) improve overall diagnostic performance, they are also limited by obligatory time for observation. "Rapid rule-out MI" protocols incorporating myoglobin do not identify patients with unstable angina and are limited by diminished specificity for MI (11 ).…”
Section: The Search For a Biomarker Of Cardiac Ischemiamentioning
confidence: 99%